Rapid method for differentiation of Trichophyton rubrum, Trichophyton mentagrophytes, and related dermatophyte species. - Summerbell, R C (1988)
Bromocresol purple-milk solids-glucose medium, proposed by Fischer and Kane in 1971 (Mycopathol. Mycol. Appl. 43:169-180, 1971) as an aid in the rapid determination of Trichophyton rubrum and Trichophyton mentagrophytes, was evaluated across a wide range of isolates to determine its accuracy and efficacy in the clinical laboratory. Results showed that it facilitated accurate determination of typical and atypical isolates of both species and also permitted the rapid identification of other closely related and similar species. Identification of all dermatophyte species tested was possible within 7 to 10 days. Occult contamination of isolates by antibiotic-resistant bacteria did not hinder identification.